Mental health in the Ruhr – Links between a neighborhood's characteristics and depression - Tom Meyer; Andreas Farwick (Wellbeing, Space and Society)
Few empirical studies have examined the impact of neighborhood context on mental health while controlling for various relevant factors. This paper addresses this gap by analyzing data from the Heinz Nixdorf Multigenerational Study (N = 2,897, age range = 18–90 years) of residents in Mülheim an der Ruhr, Essen, and Bochum (Germany) from 2013 to 2016. Using cluster-robust logistic regression, we investigated how neighborhood factors influence the likelihood of depression, accounting for individual-level characteristics.The findings indicate that high urbanization, perceived lack of nighttime safety, and especially neighborhood socio-economic disadvantage significantly increase the risk of depression, especially when considering length of residence. These results highlight the significant impact of socially disadvantaged neighborhoods on mental health, underscoring the need for targeted interventions to prevent extreme socio-spatial segregation.